Analisis Kesulitan Siswa MA Alkhairaat Kalangkangan Dalam Memecahkan Masalah Pada Materi Fluida Statis Berdasarkan Tahapan Ideal Problem Solving - Lestari Lestari; Kamaluddin Kamaluddin; Syamsu Syamsu (Universitas Tadulako, 2023)
Abstract This study aims to describe the difficulties and factors causing the difficulties of MA Alkhairaat Kalangkangan students in solving Static Fluid material problems based on the IDEAL Problem Solving stages. This research is a mixed method, with the type of research explanatory sequential mix methods. The subjects in this study were students of class XI MIA MA Alkhairaat Kalangkangan who collected 30 students. Respondents in this research category were 6 students who were selected based on high, medium and low. The data in this study were obtained from problem solving difficulty tests and interviews. The results showed that at the stage of identifying problems and possible exploration strategies, most of the respondents experienced difficulties. At the stage of setting goals, almost half of the respondents experienced difficulties. At the stage of implementing the strategy and reviewing and implementing it, respondents generally experienced difficulties. What causes respondents to experience difficulties, namely respondents cannot understand well so that respondents find it difficult to translate or change mathematical concepts, respondents cannot understand the problems that exist in the questions, respondents understand the equations used, do not understand the concepts and lack of practice, respondents are less thorough and skilled in performing arithmetic operations, as well as difficulties at the stage of determining problem objectives and exploring strategies, respondents lacked time and were not accustomed to re-examining answers.